Estudio de factibilidad para la creación de una empresa constructora “Construcasa Duque SAS” en el municipio de Santa Rosa de Cabal Risaralda (2014)
It is a business model dedicated to building small and medium scale, meeting the individual needs of each customer, whether in housing, apartment or structural arrangements, Construcasa Duque was born as an innovative idea which promotes building vertically avoiding the deterioration of the ecosystem and providing solution to the current housing deficit in the municipality. At work you can differentiate each of the stages that comprise it, well, the bill consisting of the methodological part; in it you can see the subject, description, formulation and systematization of the problem, objectives, justification, delimitation, the framework and all the methodological design. In the market research synthesis Fieldwork is an analysis of supply and demand is made, then the prices are analyzed, then the technical study is that factors such as size will identify the new organization, location and project engineering, also the administrative and legal study where the most relevant factors mentioned since this variable to legalize the construction takes place. The financial study resources needed to operate the company CONSTRUCASA DUQUE SAS and operational costs are covered, the equilibrium point is analyzed, working capital is established and credit terms are assessed. Similarly projected financial statements are made, the reasons and indicators are calculated, and the project is evaluated to establish the feasibility of the investment.